Alarm - Pascual, Joseph Victor Lee
"Alarm explores the concepts of dreaming and reality. Dreaming is shown to help release repressed desires and frustrations, but also lead to confusion between dream and reality, when the dream becomes more real than waking life. The framework for this narrative is Freud's Psychoanalytic Theory of Dreams, which discusses how dreams and the unconscious are connected. In his book The Interpretation of Dreams, Freud wrote that dreams are "...disguised fulfillments of repressed wishes." Central to this film is that idea - that maybe, when one's desires are too strong and too bottled up, dreams begin to encroach upon reality and blur the line between the two."